Membuat Aplikasi Penginputan Data Siswa pada Taman Kanak Kanak Harith Foundation Berbasis AppSheet - Swanda, Lilis; Mutia, Ainun; Kurniadi, Wisnu (Journal Software, Hardware and Information Technology, 2023)
The development of informatics technology and science is very rapid and affects the field of information and management, especially in the field of data processing using computer technology. Computer technology is something that is highly coveted by every organization, because it will produce accurate and perfect information. The need for computers as a means of solving problems quickly and precisely cannot be denied. Currently, the Harith Foundation Kindergarten manages data. Managing Student and Student data, especially in recapitulating and filtering Student and Student data, is still using MS Excel and writing manually. Therefore the purpose of this study is to make an Apsheet-based application for entering student data at the Harith Foundation Kindergarten. The method used in this study is the Waterfall method. The waterfall method is a work method that emphasizes sequential and systematic phases. This application uses the AppSheet platform to process Student and Student data at Harith Foundation Kindergarten which can be used with computers and Android operating system, with the results of making Student and Student data collection applications at Harith Foundation Kindergarten making it easier for Kindergarten Secretaries and Teachers to collect data.